FILSAFAT SOSIAL-POLITIK PLATO DAN ARISTOTELES - Alim Roswantoro (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
Plato andAristeoteles have a teacher-student relationship. And both philosophers have the same teacher, that is, a great philosopher of the classic Greek, Socrates. Both philosophers talk many things in philosophy, and one of them is the social-political thought. The writing tries to comparative-philosophically describe the social-political thought of Plato and Aristotle that can be read in their works particularly in Republic, Laws, and Statesman of Plato, and in Nicomachean Ethics and Politics ofAristotle. The result of study shows that the main idea of their social-political philosophies is to create and maintain a just city-state providing the happiness for all citizens. But, both philosophers differ in respect of the way of embodying it. InPlato's thought, a just city-state occurs under the guidance of the light of ideal knowledge and virtue produced by philosophers-kings. Whereas for Aristotle, it happens because of the human-instictive process as socil-polical creature. It takes place as along as the city• state is able to condition its citizens to be the good people.